The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1155/2021/8856687
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Secretion and Subsequent Impaired Lymphopoiesis after Starvation Can Be Reduced by Moxibustion Treatment

Abstract: As a known steroid hormone, cortisol is involved in gluconeogenesis. Uninterrupted cortisol secretion has fatal effects, both physically and psychologically, because cortisol counteracts the immune response. Moxibustion (Mox) treatment is a traditional technique used in East Asia, which therapeutically transfers heat to certain points on the body surface. In the present study, the effect of Mox treatment on stress hormone secretion was investigated using a mouse model of starvation, in which Mox was applied on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, in this study, the serum Corticosterone level of the Bio-clean II treated rats was significantly reduced in a duration dependent manner when compared to the inflammation control post-exposure to LPS. This agrees with the study of Hwang et al, in which treatment with Mox (a traditional therapeutic procedure used in Oriental Medicine for treating infectious diseases, ulcerative colitis, rheumatoid arthritis, cancer and pain) was found to significantly reduce high cortisol levels in a dose-dependent manner in mice [44]. It is also in agreement with the work of Lim et al in which Lindera obtusiloba extracts, at concentrations that were not affected by cell viability, significantly decreased luciferase activity in response to cortisol in a concentrationdependent manner [45].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in this study, the serum Corticosterone level of the Bio-clean II treated rats was significantly reduced in a duration dependent manner when compared to the inflammation control post-exposure to LPS. This agrees with the study of Hwang et al, in which treatment with Mox (a traditional therapeutic procedure used in Oriental Medicine for treating infectious diseases, ulcerative colitis, rheumatoid arthritis, cancer and pain) was found to significantly reduce high cortisol levels in a dose-dependent manner in mice [44]. It is also in agreement with the work of Lim et al in which Lindera obtusiloba extracts, at concentrations that were not affected by cell viability, significantly decreased luciferase activity in response to cortisol in a concentrationdependent manner [45].…”
Section: Discussionsupporting
confidence: 92%
“…The effect of moxibustion on stress, including stress hormones and sympathetic activity, has primarily been investigated in stress-induced animal models [23,24]. In terms of clinical studies, there has been only one study examining the effect of moxibustion on stress-related variables [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited evidence regarding the effectiveness of moxibustion on stress. Studies have reported the effects of moxibustion on stress hormones (i.e., cortisol) in stressed animal models with conditions like starvation and gastric ulcer [23,24], but its effects on stress hormones in human individuals are not yet established. The effect of moxibustion on mental stress is currently unknown.…”
Section: Introductionmentioning
confidence: 99%